2012
DOI: 10.4172/2157-7145.1000149
|View full text |Cite
|
Sign up to set email alerts
|

Medico-Legal Age Estimation in Living Individual from a Portuguese Population: Third Molar Mineralization

Abstract: According to the Study Group on Forensic Age Diagnostics (AGFAD), the radiological evaluation of third molar mineralization is a major criterion for chronological age estimation of living individuals.This investigation studied third molar development in 329 orthopantomograms (40.4% males) of Portuguese individuals, patients of Dental Medicine Faculty of Lisbon University, with an age range between 14,0 to 22,8 years, through five different methods (Demirjian, Haavikko, Harris and Nortjè, Kullman and Solari).Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
0
0
Order By: Relevance
“…The present finding, therefore, answers the question of whether a person is already 18 years of age by high degree confidence and considered as an adult. This finding is substantiated by Garamendi et al (7) and another study done in Portugal that found females and males reach the age 18 years in stages (G) and (H) respectively (14) , in other studies done in Turkey and Japan, the mineralization of third molars are the same in both sexes (12,20,21) , wereas other studies on population from China, Saudi Arabia, Australia and Indonesia showed that the age 18 years is reached in stage (H) in males earlier than females (5,9,15,26,32) .…”
Section: Resultssupporting
confidence: 65%
“…The present finding, therefore, answers the question of whether a person is already 18 years of age by high degree confidence and considered as an adult. This finding is substantiated by Garamendi et al (7) and another study done in Portugal that found females and males reach the age 18 years in stages (G) and (H) respectively (14) , in other studies done in Turkey and Japan, the mineralization of third molars are the same in both sexes (12,20,21) , wereas other studies on population from China, Saudi Arabia, Australia and Indonesia showed that the age 18 years is reached in stage (H) in males earlier than females (5,9,15,26,32) .…”
Section: Resultssupporting
confidence: 65%